Impact of primary site on survival in patients with nasopharyngeal carcinoma from 2004 to 2015 - Shen, Tianyi; Cai, Wenting; Li, Tingting; Yu, Donghui; Ren, Chengda; Yu, Jing (Frontiers in Surgery, 2022)
Background Nasopharynx carcinoma (NPC) is the most common malignant tumor of the nasopharynx. Many studies have shown some factors related with the prognosis of NPC patients. Our study aims to evaluate the differences of prognosis between initial and second primary NPC. Material and methods The Surveillance, Epidemiology, and End Results (SEER) program was used to perform the population-based analysis in NPC patients who were newly diagnosed between 2004 and 2015. Kaplan-Meier and Cox regressions were used to evaluate the effects of primary site on the overall survival (OS), as well as the cancer-specific survival (CSS). Results Our study included 5,012 NPC patients: 4,474 initial primary NPC patients and 5,38 s primary NPC patients. Significant differences were observed in sex, age at diagnosis, race, median household income, histological type, American Joint Committee on Cancer (AJCC) stage, N-stage, radiation treatment and chemotherapy between patients with initial and second NPC (P < 0.05). Moreover, the patients with second NPC had longer survival months. In addition, radiation and chemotherapy were recommended both in first and second primary NPC patients. Conclusion Worse prognosis was observed in patients with second primary NPC compared with those with primary NPC in all subgroups of AJCC stage and age at diagnosis.